THE REPERCUSSIONS OF SEXUAL ASSAULT TO CHILDREN: A PSYCHOPATHOLOGICAL LOOK AT THREE OBSERVATIONS AND ANALYSIS OF DRAWINGS IN SOUTH KIVU, DEMOCRATIC REPUBLIC OF THE CONGO - Philippe , Amani Busane; Degauli, Boris Houga; Marie-Grace, Kaboyi Kira; Denis, Mukwege Mukengere; Camara, Momar; Fall, Lamine (IJRDO - Journal of Social Science and Humanities Research, 2023)
Objective: is to determine the psychological repercussions of sexual assault and its socio-cultural representations on the life of the child who is a direct victim and his mother. Method: This is a descriptive qualitative study with an analytical aim on three child victims of sexual violence, whose ages vary between two and six years. It was conducted in South Kivu, DRC, over a one-year period from January 2019 to January 2020. To assess the degree of suffering of the children, we used free drawing and semi-structured interviews with the parents Results: The children showed many signs of suffering, both physical and psychological. Beyond this personal situation, the context was weighed down by social considerations. These had the value of a second trauma as they maintained the first trauma and offered a practically impossible future. The drawing had proved to be a good indicator of this trauma. The processes of psychic reorganisation could be observed, as well as chaotic situations of diffuse suffering. The families, especially the mothers, had also participated in the management of this traumatic event. The mothers’ restraining attitudes had helped these girls a great deal. This advantage diminished when the social values of rejection were introduced into the family, thus reinforcing the devaluation of the victim. The personal history of each of the girls in our study could also influence the way in which they dealt with the harm. Conclusion: Secure extrinsic input is necessary for the resilience of these three girls.